Cyrtodactylus martini, another new karst-dwelling Cyrtodactylus Gray, 1827 (Squamata: Gekkonidae) from Northwestern Vietnam - van Tri, Ngo (Zootaxa, 2011)
A new species of karst–dwelling bent–toed gecko, Cyrtodactylus martini sp. nov., is described from the isolated karst formations of the Hoang Lien Son Mountain range in northwestern Vietnam. It differs from all other congeners by the presence of symmetrical or subsymmetrical reticulations on top of head; no nuchal loop; four precloacal pores separated medially by one poreless scale; 14–18 enlarged femoral scales beneath thighs continuous with precloacal scales; four to six irregular, narrow, yellowish–white bands on dorsum between limb insertions; and six or seven incomplete white rings on tail.